2011
DOI: 10.1111/j.1365-2699.2011.02550.x
|View full text |Cite
|
Sign up to set email alerts
|

SESAM - a new framework integrating macroecological and species distribution models for predicting spatio-temporal patterns of species assemblages

Abstract: Two different approaches currently prevail for predicting spatial patterns of species assemblages. The first approach (macroecological modelling, MEM) focuses directly on realized properties of species assemblages, whereas the second approach (stacked species distribution modelling, S‐SDM) starts with constituent species to approximate the properties of assemblages. Here, we propose to unify the two approaches in a single ‘spatially explicit species assemblage modelling’ (SESAM) framework. This framework uses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
475
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 396 publications
(501 citation statements)
references
References 85 publications
6
475
1
2
Order By: Relevance
“…Ferrier 2002), it provides a first approximation to the geographic variations of species diversity in the absence of good quality data on species distributions or composition, which is more prone to error (see Hortal et al 2007;Pineda & Lobo 2009;Aranda & Lobo 2011 for comparisons of both kinds of data). Being based in a simpler variable, it also provides a simpler way of analyzing the effects of data quality on model reliability; we assume that the results of this study can be extrapolated to ALM applications based on other aspects of biodiversity (see Hortal & Lobo 2006;Guisan & Rahbek 2011). Thus, here we compare the adequacy of GLM and kriging to interpolate richness values.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ferrier 2002), it provides a first approximation to the geographic variations of species diversity in the absence of good quality data on species distributions or composition, which is more prone to error (see Hortal et al 2007;Pineda & Lobo 2009;Aranda & Lobo 2011 for comparisons of both kinds of data). Being based in a simpler variable, it also provides a simpler way of analyzing the effects of data quality on model reliability; we assume that the results of this study can be extrapolated to ALM applications based on other aspects of biodiversity (see Hortal & Lobo 2006;Guisan & Rahbek 2011). Thus, here we compare the adequacy of GLM and kriging to interpolate richness values.…”
Section: Introductionmentioning
confidence: 99%
“…While SDM techniques are widely used to project species distributions into different geographical and temporal scenarios (see Lobo et al 2010), ALMs receive less attention as predictive tools, being more used to study the relationships between diversity and environment (e.g. Lobo et al 2001; see also Guisan & Rahbek 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drawbacks include the lack of speciesspecific information and the potential smoothing or generalization of spatial predictions due to a loss of biological connection with covariates, depending on how species are grouped. Research comparing the different modeling strategies for v www.esajournals.org estimating species richness from occurrencebased models has yielded mixed results about differences in model predictions (Ferrier et al 2002, Lehmann et al 2002, Guisan and Rahbek 2011, Hallstan et al 2012). To our knowledge, our work represents the first comparison of these different strategies for SAMs.…”
Section: Introductionmentioning
confidence: 99%
“…This class of analysis is macro-ecological analysis using models for species richness and turnover (Ferrier & Guisan 2006;Arponen et al 2008;Guisan & Rahbek 2011;Mokany & Ferrier 2011). Arponen et al (2008) identified the components needed for successful ecological communitylevel decision analysis, including statistically justified simultaneous handling of species richness and pair-wise similarity of ecological communities, modeled as functions of environmental conditions.…”
Section: Environmental Surrogacy and Planning With Scarce Datamentioning
confidence: 99%